1999
DOI: 10.3354/meps176093
|View full text |Cite
|
Sign up to set email alerts
|

Sex change and female dimorphism in Calanus finmarchicus

Abstract: ABSTRACT. Adult females were examined from November until spring in northern Norway (30" N) to determine the fraction with the quadrithek and the fraction with the trithek setal pattern on the antennule. The quadrithek (Q) pattern is a male characteristic in which odd numbered, proximal segments carry 2 aesthetascs and 2 setae; the trithek (T) pattern has 1 aesthetics on all antennular segments. The frequency of quadrithek females (%Q = 100 X [Q/T]) varied with season. It peaked at 38% in February, declining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Other mechanisms of sexratio control may be invoked. There is circumstantial evidence that copepods of the family Calanidae may change sex in the course of development (Flemminger 1985;Svensen and Tande 1999;Irigoien et al 2000;Miller et al 2005), as has been demonstrated in other copepods (see review by Miller et al 2005), and that sex-determination may be under environmental control (reviewed by Mauchline 1998). The pronounced seasonal variation in sex-ratio, exceeding the expectation based on a simple population dynamics model, makes further examination of sex-determination in pelagic copepods potentially rewarding.…”
Section: Patterns In Sex Ratiomentioning
confidence: 93%
“…Other mechanisms of sexratio control may be invoked. There is circumstantial evidence that copepods of the family Calanidae may change sex in the course of development (Flemminger 1985;Svensen and Tande 1999;Irigoien et al 2000;Miller et al 2005), as has been demonstrated in other copepods (see review by Miller et al 2005), and that sex-determination may be under environmental control (reviewed by Mauchline 1998). The pronounced seasonal variation in sex-ratio, exceeding the expectation based on a simple population dynamics model, makes further examination of sex-determination in pelagic copepods potentially rewarding.…”
Section: Patterns In Sex Ratiomentioning
confidence: 93%
“…), where there are 2 strong generations each year, showed 66% Q females (N = 63) in March, 4%Q (N = 52) in May. The initial fraction exceeds Svensen & Tande's (1999) February result, and the seasonal change in fraction is in the same direction and greater than that at Georges Bank. Both observations strengthen the conclusion that sex determination varies with differences in habitat, suggesting that it is an adaptive mechanism.…”
Section: Variation In Proportions Of Quadrithek Females In a Life-cycmentioning
confidence: 87%
“…Svensen & Tande (1999) determined the fraction of Q females of C. finmarchicus in Malangen Fjord in northern Norway near Tromsø, where more than 95% of the stock completes only a single life cycle in the year (Tande 1982). They found 38% Q in February (early maturers) and 25% in March.…”
Section: Variation In Proportions Of Quadrithek Females In a Life-cycmentioning
confidence: 99%
“…Due to the short period simulated, we also assumed zero mortality. The sexratio was set to 50%, indicating that moulting CVs split equally into male and females at this time of the year (Svensen & Tande 1999).…”
Section: Methodsmentioning
confidence: 99%